Phenomenon of parliamentarism in the societies of the post-socialist transformation: problems of institutionalization (Journal of Philosophy Culture and Political Science, 2018)
For the societies of post-socialist transformation was extremely topical issue of choosing the model rule and implementing it in practice. The paper discusses the advantages of parliamentary government and highlighted the factors that give rise to difficulties in the ways of its development and implementation of the political system transforming societies. Key words: democracy, parliamentarism, parliamentary, representation of the people, the principle of separation of powers, transitional society, modernization.